STUDY ON THE EFFECT OF TEMPERATURE ON THE OPERATION OF THE PANASONIC NCR-18650B ELECTRIC VEHICLE BATTERY - Nguyen Phi Cuong Anh; Le Duc Hieu; Luong Ngoc Minh (Tạp chí Khoa học, 2024)
This paper focuses on studying the influence of temperature on the working process of Panasonic NCR-18650B electric vehicle battery. Through the Matlab - Simulink simulation tool, the effects related to the charging/discharging process of electric vehicle batteries such as voltage, current and state of charge (SOC) have been considered at different temperature of 0, 25, 50 degrees Celsius. Research results contribute to optimizing battery usage, thereby minimizing the impact of batteries on the environment, contributing to the development of the current electric car industry.